Using Cluster Approach to Forming Regional Policy in Ukrainian Black Sea Region: Array - Soroka, Larysa (Journal of Danubian Studies and Research, 2020)
It is shown how the tools and directions for competitiveness depend on many factors, including the economic growth rate of some country and region. But one of the universal tools of increasing the competitiveness of the economy is using cluster models of development.. The cluster model implementation efficiency is achieved by forming scientifically grounded with pre-planned regional development policy studies. According to the results of the research, a systematic cause-andeffect relationship between the creation of cluster systems and an increase in the competitive capacity of economic systems has been identified. This gives the reason to argue that clusters are an instrument of increasing the competitiveness of national economies in the context of globalization. Based on the research conducted on the example of the Ukrainian Black Sea, the following conclusions were drawn: the implementation of the cluster policy is based on the organization of interaction between state authorities and local self-government, business, science, education, production; there is a variety of forms and methods for providing cluster policies that differs by national features, the cluster approach concept; using the cluster approach can be considered as natural stage of the country’s economy development; clusters are a specific form of innovation, and innovation is an important factor in enhancing competitiveness; the specificity of the cluster is to obtain a synergistic effect, which is expressed in increasing competitiveness, and its distinctive feature is innovative orientation; clusters contribute to the growth of tax revenues to budgets; clusters stimulate the development of small and medium-sized businesses.